A STUDY ON THE INFLUENCE OF PLACE AND EDUCATION ON MUSLIM WOMEN EMPOWERMENT - Shahzad Hasan; Shilan Abdulkarim (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The main objective of the study is to determine whether there is any significant difference in women’s empowerment based on their locality and qualification. The data collected for this study was from 200 women at Coimbatore District. Urban and rural locality women are not differing significantly in violence, but the rural women are facing more empowerment in the dimensions of education, social status, finance, marriage, gender equality and overall dimensions the empowerment than the urban women. Below graduate, graduation,  above graduate qualified women’s are not differing significantly in education, social status, finance, violence, gender equality and over all dimensions, but the below graduate  women are facing more problem in the dimensions of ‘marriage’ in the women empowerment than the other qualified women